PENGARUH MEDIA PENDINGIN PADA PROSES HARDENING MATERIAL BAJA S45C - Syaifudin Yuri; Sofyan Djamil; Sobron Yamin Lubis (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Hardening is the process of heating the steel to a temperature of austenite and then dyeing is done quickly, the process is carried out to improve the properties of steel hardness. The method used in this research using books and journal literature .The purpose of this study to determine the mechanical properties of the steel that is cooled by the cooling medium brine , oil, water and air in the cooling medium to the level of violence after the S45C steel is hardened in a hardening process and microstructure . The study starts from the cutting hardness test specimen with a diameter of 65 mm x 7 mm x 10 mm and impact test with a diameter of 10 mm x 10 mm x 55 mm . The results obtained hardness test salt water has the average value of hardness 95 BHN , the average value of hardness oli 89 BHN , the average value of water hardness 94 BHN , the average value of hardness air 87 BHN and hardness values without in hardening 88 BHN , impact test on the air has an average value 1.175 J/